ChemInform Abstract: Broensted Acid‐Catalyzed Chemodivergent Reactions of ortho‐Mercaptobenzyl Alcohols with 3‐Alkyl‐2‐vinylindoles and Styrenes: [5 + 2] Cyclization versus Hydroxysulfenylation. Issue 34 (4th August 2016) - Zhao, Jia‐Jia; Tang, Man; Zhang, Hong‐Hao; Xu, Meng‐Meng; Shi, Feng
Abstract: The BNPA‐catalyzed reaction of 2‐mercaptobenzyl alcohols (II) with 2‐vinylindoles (I) leads to benzoxathiepines (III), whilst reactions with indene (IV) and alkenes (VI) under similar conditions give rise to corresponding β‐hydroxy sulfides.